Effects of the whole-body cryotherapy on NTproBNP, hsCRP and troponin I in athletes - Banfi, G.; Melegati, G.; Barassi, A.; Melzi d`Eril, G. (Journal of Science and Medicine in Sport, 2009)
Whole-body cryotherapy refers to brief exposure to very cold air for treating symptoms of various illnesses. In sports medicine, whole-body cryotherapy is administered to improve recovery from muscular trauma. As specific studies are lacking, we measured cardiac markers in 10 top-level rugby players of the Italian National team before and after a 1-week course of daily sessions of whole-body cryotherapy. All subjects continued with the same training workload as that of the previous weeks. N-terminal pro B-type natriuretic peptide (NTproBNP) levels increased but remained within the normal range, whilst troponin I (TnI) and high sensitivity C-reactive protein (hsCRP) were unchanged. Whole-body cryotherapy did not impair cardiac function in this sample of elite athletes.